The star cluster age-metallicity relationship in the Small Magellanic Cloud - Piatti, Andres Eduardo (2012)
We present CCD Washington photometry of 11 Small Magellanic Cloud (SMC) clusters for which age and metallicity estimates are provided. The 11 clusters are witnesses of the ∼ 2 Gyr bursting formation episode, according to their positions in the age-metallicity relationship (AMR). We added these clusters to the largest known SMC cluster sample with ages and metallicities put into an homogeneous scale, and found that two enhanced formation episodes at t ∼ 2 and 5-6 Gyr throughout the entire body of the galaxy, the absent of a metallicity gradient and a relative spread in metallicity for clusters older than ∼ 7 Gyr comprehensively describe the SMC AMR. In addition, based on the statistics of catalogued and studied clusters, we found that a total of seven relatively old/old clusters have not yet studied, and even a smaller number is obtained if the cluster spatial distribution is considered. A detailed version of this work can be seen in Piatti (2011, MNRAS, 418, L73).